The sound and face of others: vocal priming effects on facial emotion processing in posttraumatic stress disorder - Schneider, Isabella; Bertsch, Katja; Izurieta Hidalgo, Natalie A.; Müller, Laura Elisa; Defiebre, Nadine; Herpertz, Sabine (Psychopathology, 2019)
Introduction: Facial expressions and vocal intonation are key signals in the communication of emotions. Individuals with posttraumatic stress disorder (PTSD) are known to show an impaired perception of facial emotions. So far, research on multimodal emotional stimuli or the priming effects on emotion processing has been absent in PTSD. Therefore, we conducted a study to investigate the influence of vocal priming on facial emotion processing and classification in PTSD using electroencephalography. Methods: Twenty-one women with PTSD compared to 28 healthy women were asked to classify emotion-morphed faces with predominantly angry, ambiguous, or predominantly happy expressions primed by either an angry or a happy voice. Responses and reaction times as well as the N170, a component reflecting configural face processing, were analyzed. Results: Patients with PTSD were slower in classifying emotional faces that were primed by either an angry or happy voice compared to the healthy controls (HCs; η2 = 0.14). Additionally, patients with PTSD were faster in classifying facial expressions after angry compared to happy vocal primes (η2 = 0.14). HCs did not show this effect. Correlation analyses revealed positive associations between emotion (dys-)regulation and reaction times in patients with PTSD but not in HCs (r = 0.64-0.76). Furthermore, patients with PTSD showed greater N170 amplitudes for predominantly angry and ambiguous faces than HCs (η2 = 0.07). Conclusion: Data suggest that patients with PTSD experience more difficulties when processing complex social stimuli than HCs. The altered processing of complex social-emotional signals could amplify PTSD symptoms, thus qualifying as an explicit therapy target.
Gesehen am 17.02.2020